2021
DOI: 10.1111/jphd.12475
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning and dental caries among preschool children

Abstract: Objectives To investigate the relationship of family functioning with dental caries among 3–4‐year‐olds and the role of family functioning in explaining the relationship of family socioeconomic status (SES) with childhood dental caries. Methods Data from 761 parent–child dyads who took part in the East London Oral Health Inequalities study were analyzed. Family functioning was assessed using the 60‐item family assessment device that yielded scores on general functioning and six domains (roles, communication, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The findings showed that participants had grown up in a secure environment, with supportive, responsive caregivers and a family that was resilient and able to solve problems. Previous studies have shown the importance of family functioning, such as responsiveness, involvement, encouragement, and problem‐solving, for good oral health and oral health behaviour in their children [34–37]. This association has also been observed in socioeconomically vulnerable populations [38, 39].…”
Section: Discussionmentioning
confidence: 82%
“…The findings showed that participants had grown up in a secure environment, with supportive, responsive caregivers and a family that was resilient and able to solve problems. Previous studies have shown the importance of family functioning, such as responsiveness, involvement, encouragement, and problem‐solving, for good oral health and oral health behaviour in their children [34–37]. This association has also been observed in socioeconomically vulnerable populations [38, 39].…”
Section: Discussionmentioning
confidence: 82%
“…A final explanation is that a healthy level of interaction between family members might provide a psychosocial environment that is conducive to health‐promoting behaviours, child oral health and good quality of life. This potential pathway is supported by evidence showing that unhealthy family functioning was associated with greater sugar intake and less frequent toothbrushing among young children 26,27 . Both behaviours are established determinants of dental caries, 28 which is, in turn, a common oral disease affecting child and family quality of life 6…”
Section: Discussionmentioning
confidence: 93%
“…This potential pathway is supported by evidence showing that unhealthy family functioning was associated with greater sugar intake and less frequent toothbrushing among young children. 26,27 Both behaviours are established determinants of dental caries, 28 which is, in turn, a common oral disease affecting child and family quality of life. 6 This study also highlighted which domains of family functioning could be more relevant to the OHRQoL of children and their families.…”
Section: Discussionmentioning
confidence: 99%
“…The limited evidence indicates that positive parenting approaches work best to produce favourable oral hygiene behaviours in children, and lead to better oral health outcomes [5,36,37]. Previous research has also established that poor family functioning leads to poor oral health outcomes in children [38]. However, no study so far has examined the association between parenting practices and the impact of children's health on the family in the context of childhood oral diseases.…”
Section: Discussionmentioning
confidence: 99%